2017
DOI: 10.1016/j.phrs.2017.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Taltirelin alleviates fatigue-like behavior in mouse models of cancer-related fatigue

Abstract: Fatigue affects most cancer patients and has numerous potential causes, including cancer itself and cancer treatment. Cancer-related fatigue (CRF) is not relieved by rest, can decrease quality of life, and has no FDA-approved therapy. Thyrotropin-releasing hormone (TRH) has been proposed as a potential novel treatment for CRF, but its efficacy against CRF remains largely untested. Thus, we tested the TRH analog, taltirelin (TAL), in mouse models of CRF. To model fatigue, we used a mouse model of chemotherapy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…Research toward these goals requires preclinical models of fatigue, preclinical assays to measure fatigue-like behavior, and knowledge that fatigue-like behavior is being detected by the assay. Numerous models of fatigue are in use, including a variety of CRF models [6][7][8][9] as well as inflammation-induced fatigue models intended to recapitulate aspects of other disorders, such as CFS/ME and SS [10][11][12]. Although these models cannot fully replicate human fatigue, they can provide valuable tools for understanding potential causes of fatigue and identifying potential biomarkers and therapeutics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research toward these goals requires preclinical models of fatigue, preclinical assays to measure fatigue-like behavior, and knowledge that fatigue-like behavior is being detected by the assay. Numerous models of fatigue are in use, including a variety of CRF models [6][7][8][9] as well as inflammation-induced fatigue models intended to recapitulate aspects of other disorders, such as CFS/ME and SS [10][11][12]. Although these models cannot fully replicate human fatigue, they can provide valuable tools for understanding potential causes of fatigue and identifying potential biomarkers and therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…We focused on a single mouse model of fatigue, inducing fatigue via injections of a cytotoxic chemotherapy drug, 5-fluorouracil . This model was selected because prior studies have shown it induces fatigue-like behavior as measured by VWRA [16,29] and, at a lower dose, 5-FU also induces fatigue-like behavior in the TFT [6]. Additionally, we tested two potential anti-fatigue therapeutics, taltirelin (TAL) and methylphenidate (MPH), to determine if any observed fatigue-like behavior was alleviated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although fatigue is considered to be a multidimensional behavior, it is mostly manifested as a decline in physical function and daily activity 6 . Much of the published work on mouse models of fatigue focuses on cancer-related fatigue, which can be induced by tumor growth 7 10 , chemotherapy 10 15 , or radiation 10 , 16 , 17 . Other published studies induce fatigue using lipopolysaccharide 18 or exercise 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…In clinical studies, fatigue is typically determined by self-reports and questionnaires, and rarely using behavioral or physical measurements 2 . In contrast, with preclinical mouse models investigators have published quite a few behavioral measures of physical activity to measure fatigue, including: running wheels 7 9 , 11 , 12 , 14 – 17 , 20 , 21 ; home cage monitoring using video 7 , 8 , 18 , telemetry 11 , or cages with light beams/sensors 20 ; treadmills 10 , 19 , 21 ; forced swim 8 , 9 ; and open field 12 . However, there are no standards for which methods should be considered reliable indicators of fatigue.…”
Section: Introductionmentioning
confidence: 99%